Rigid ceramic filters: numerical simulation of the pressure & velocity distributions - Abdullah, Luqman Chuah (Universiti Putra Malaysia Press, 2017)
Tightened environmental legislation enacted as a result of government policy has compelled the industry to pay serious attention to air pollution issues. Gas cleaning with ceramic filters has proven to be a major technology for removal of particulate emissions at high temperatures. Filters, after a certain period of filtration time, must be cleaned for maximum efficiency. This can be done by applying a pulsed reverse cleaning flow into the filters. The cleaning mechanisms by which the deposited cake is removed from the filter surface are still not fully understood. Varied mathematical models were thus developed to investigate the flow dynamics of the filtration and reverse pulse flow cleaning in a ceramic filter. These include a Computational Fluid Dynamics (CFD) model, a Simple Excel Reverse Pulse Flow Model and a time-dependent filter cake model. The simulation results were validated using the results of previously reported experiments carried out for filtration and reverse flow cleaning using the filter elements.